An Efficient and Facile Synthesis of 5‐(Thiophene‐2‐carbonyl)‐6‐(trifluoromethyl)‐tetrahydro‐pyrimidin‐2(1H)‐one and 6‐(Thiophen‐2‐yl)‐4, 5‐dihydropyrimidin‐2(1H)‐one from Same Substrates Under Different Conditions. (22nd December 2014) - Liang‐Ce, Rong; Zha, Yunyun; Xia, Sheng; Ji, Linlin; Zhang, Jing; Cai, Peijun
Abstract : A series of 5‐(thiophene‐2‐carbonyl)‐6‐(trifluoromethyl)‐tetrahydropyrimidin‐2(1 H )‐one and 6‐(thiophen‐2‐yl)‐4, 5‐dihydropyrimidin‐2(1 H )‐one derivatives have been synthesized from the reactions of aromatic aldehydes, 4, 4, 4‐trifluoro‐1‐(thien‐2‐yl)butane‐1, 3‐dione and urea under the different conditions with high yields. In this research, it was found that the p ‐toluenesulfonic acid was an efficient catalyst for obtaining 5‐(thiophene‐2‐carbonyl)‐6‐(trifluoromethyl)‐tetrahydropyrimidin‐2(1 H )‐one derivative. At the same time, solvent‐free and NaOH were the preferred conditions for the synthesis of 6‐(thiophen‐2‐yl)‐4, 5‐dihydropyrimidin‐2(1 H )‐one derivative. Moreover, because of short reaction time, excellent yields, simple setup, this research offered an efficient process for preparing these kind compounds. Abstract :